Diwan 'Antarah ibn Shaddad A Literary-Historical Study - Montgomery, James E. 1962- (Library of Arabic Literature, 2018)
The pre-Islamic warrior-poet 'Antarah ibn Shaddad, a composer of one of the Mu'allaqat, attracted the attention of the philologists who were active in Iraq at the nascence of the scholarly study of Arabic. These philologists collected and studied the diwan of 'Antarah as part of their recovery and codification of the Jahiliyyah: 'Antarah became one of the Six Poets, a collection of pre-Islamic poets associated with al-Asma'i, "the father of Arabic philology." Two centuries later, in al-Andalus, al-Shantamari and al-Batalyawsi composed their commentaries on the diwans of the Six Poets. This study uncovers the literary history of 'Antarah’s diwan and presents five editions, with critical apparatus, of the extant recensions, based on an extensive collation of the surviving manuscripts